Utilization of Industrial Waste (Bottom Ash) as an Alternative Material in Paving Block Manufacturing - Sartika, Sartika; Aqla, Syarifah; Firman, Firman; Megasukma, Yosa (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
Coal is a heterogeneous, combustible material composed of various components with differing properties. The combustion process of coal in coal-fired power plants (CFPPs) generates waste in the form of bottom ash residue. If not properly utilized, bottom ash has The ability to trigger adverse environmental impacts. One alternative for its utilization is as a mixture component in the production of paving blocks. This study aims to evaluate the water absorption, compressive strength, and quality classification of paving blocks with the addition of bottom ash, where the test results will be compared with the Indonesian National Standard (SNI) to determine conformity to quality standards. According to the study, it can be seen that increasing the percentage of bottom ash leads to a higher water absorption rate and a decrease in compressive strength. This trend is attributed to the reduction in bulk density of the paving blocks as the proportion of bottom ash increases. Based on the test results, paving blocks without bottom ash (Sample A) fall into Class C; mixtures with 10% and 20% bottom ash (Samples B and C) fall into Class B; the 30% mixture (Sample D) belongs to Class C; and the 40% mixture (Sample E) is categorized as Class D. All composition variations meet the quality classification criteria stipulated in the applicable Indonesian National Standard (SNI). Based on compressive strength and water absorption parameters, the optimal bottom ash composition ranges between 10% and 20%.